Stereotactic Body Radiotherapy Treatment for Recurrent, Previously Irradiated Head and Neck Cancer. (11th June 2018) - Stanisce, Luke; Koshkareva, Yekaterina; Xu, Qianyi; Patel, Ashish; Squillante, Christian; Ahmad, Nadir; Rajagopalan, Kumar; Kubicek, Gregory J.
Purpose: Locally recurrent, previously irradiated primary head and neck tumors have historically been associated with poor outcomes. Stereotactic body radiation therapy has emerged as a feasible and promising treatment option for tumor recurrence, particularly in nonsurgical candidates. This study aimed to assess the associated outcomes of stereotactic body radiation therapy used in this setting. Methods: Retrospective analysis of a prospectively collected database of 25 patients treated with CyberKnife for unresectable, recurrent head and neck cancer in a previously irradiated field. The primary end points evaluated were rates of survival, tumor control, and treatment-related toxicities. Results: Median survival of the study population was 7.5 months (range, 1.5-47.0 months). Median survival of the 20 (80%) patients who were treated with curative purpose was 8.3 months. One-year overall survival rate for the entire population was 32%. The respective 1-year and 2-year survival rates for the curative subcohort were 40% and 20%, respectively. Local and locoregional failure occurred in 8 (32%) and 7 (28%) patients, respectively. Low severe acute (4%) and late (6%) treatment-related toxicity rates were observed. No grade 4 or 5 toxicities were observed. Conclusion: Stereotactic body radiation therapy is a viable treatment option for patients with unresectable, recurrent head and neck cancer. Significant tumor control rates are achievable with minimal severe toxicity. Although perhaps associated with patient selection and a heterogeneous sample, overall survival of stereotactic body radiation therapy outcomes appears unfavorable.